Analisis Pengaruh Faktor Internal dan Eksternal terhadap Pembiayaan pada Bank Muamalat Indonesia - Ainun Nuraisiah; Iwan Setiawan; Benny Barnas (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Capital Adequacy Ratio and Third-Party Funds as bank internal factors that can affect financing, while bank external factors are inflation and money supply. Secondary data types for 2010-2022 were obtained from the official websites of OJK, BI, and BMI. The research method uses multiple linear regression model analysis which has the output variable DPK having a positive and significant effect, while CAR and JUB have a partially significant negative effect on BMI financing. Inflation has no effect on financing. Simultaneously all independent variables namely CAR, DPK, Inflation, and JUB have a significant effect on financing.